A Single-Arm Phase 2 Trial on Induction Chemotherapy Followed by Concurrent Chemoradiation in Nasopharyngeal Carcinoma Using a Reduced Cumulative Dose of Cisplatin - Xu, Zhiyuan; Yang, Li; Ng, Wai-Tong; Helali, Aya El; Lee, Victor Ho-Fun; Ma, Lingyu; Liu, Qin; Li, Jishi; Shen, Lin; Huang, Jijie; Zha, Jiandong; Zhou, Cheng; et al. (Frontiers in Oncology, 2022)
Background: We conducted this study to evaluate if a reduced cumulative dose of induction and concurrent cisplatin conferred similar favorable outcomes when compared to trial NPC-0501. Methods: Newly diagnosed nasopharyngeal carcinoma (NPC) with stage III-IVA were prospectively recruited from January 2015 to September 2019. Induction chemotherapy (IC) consisted of cisplatin 80mg/m2 on day 1 and capecitabine 1000mg/m2 twice daily from day 1 to 14 every 3 weeks for 3 cycles followed by concurrent chemoradiotherapy (CCRT) with 2 cycles of cisplatin 100mg/m2 given every 3 weeks. Tumor response was evaluated according to RECIST v1.1. Acute and late adverse events (AEs) were graded with CTCAE v4.0 and Late Radiation Morbidity Scoring of the RTOG, respectively. Results: 135 patients were recruited. At 16 weeks after CCRT, 130 patients completed the entire course of radiotherapy (RT). All of whom had a complete response upon final assessment. With a median follow-up of 36.2 months, 22 treatment failures and 8 deaths were observed. The 3-year progression-free survival, overall survival, locoregional recurrence-free survival, and distant recurrence-free survival were 83.7%, 94.1%, 94.1%, and 85.9%, respectively. Our survival data outcomes were similar to those reported in the cisplatin and capecitabine (PX) induction arm of the 0501 trial. 103 patients (76.3%) reported acute grade 3-4 AEs. Two patients (1.5%) had late grade 3-4 complications, numerically fewer than those reported in the NPC-0501 trial. Conclusions: Induction PX and concurrent cisplatin with a reduced cumulative cisplatin dose yield survival outcomes comparable to those reported in the NPC-0501 trial with excellent tolerability. Therefore, a reduced cumulative dose of cisplatin is a promising treatment scheme for nasopharyngeal carcinoma.